The Impact of Oral Collagen Supplementation on Joint Function, Muscle Recovery, and Musculoskeletal Health in Athletes: A Narrative Review - Gołda, Joanna; Mężyk, Julia; Snopkowska, Aleksandra; Gacka, Piotr; Dołęga, Marcin; Dróżdż, Olgierd; Musialska, Dominika (Journal of Education, Health and Sport, 2024)
The purpose of this review is to evaluate the effects of oral collagen supplementation on joint function, muscle recovery, and overall musculoskeletal health in athletes. Collagen, a key protein in the body, is essential for the health of joints, muscles, and connective tissues. As collagen production declines with age, supplementation has become a promising strategy for improving athletic performance and reducing injury risk. This review analysed recent studies published from 2016 onwards, focusing on the impact of collagen supplementation, particularly in combination with regular training. The research involved a comprehensive literature search in the MEDLINE database, initially identifying 82 records, with 39 undergoing quality assessment. Ultimately, 26 studies met the inclusion criteria and were included in the final analysis. The findings indicate that collagen peptides significantly enhance joint stability, reduce pain, and accelerate recovery from injuries such as Achilles tendinopathy. Moreover, collagen supplementation combined with resistance training was shown to improve muscle strength, body composition, and recovery markers more effectively than training alone. The review also highlights collagen's role in extracellular matrix remodelling and anti-inflammatory responses, offering potential benefits in tissue repair and injury prevention. These results suggest that collagen supplementation could be a valuable addition to athletes' training regimens, warranting further research to optimize dosing strategies and explore its mechanisms of action.